The nature of social integration in post-apartheid Cape Town - Lemanski, C (2006)
﻿ This research considers the nature of social integration between individuals living in desegregated neighbourhoods in post-apartheid Cape Town. Social integration is understood as a dynamic process between individuals from apartheid's different racial classifications as opposed to the common emphasis in the literature on the static outcome of a neighbourhood being integrated. The research was based on both quantitative and qualitative methods. A quantitative analysis of South Africa's 2001 census results was conducted. From this analysis neighbourhoods in Cape Town with "multiple population dominance', where no single group comprises more than 50% of the suburb population and at least one other group comprises over 25%, were identified. Qualitative fieldwork (semi-structured interviews and mental maps) was conducted in two of these 'multiple population dominance' suburbs. Based on research in these neighbourhoods I conclude that labelling a suburb as physically desegregated implies a level of social cohesion that was not found, and masks the reality of division based on length of tenure and socio-economic status. Within the specific South African context of racial inequality, such opposition to desegregation that is not matched by a shared class is likely to restrict the potential for social integration to develop beyond the confines of black middle-classes moving into 'White' areas, and poor Coloureds and Black Africans living in low-cost housing, thus affecting only a handful of the population.